Acute endovascular reperfusion treatment in patients with ischaemic stroke and large‐vessel occlusion (Denmark 2011–2017). (19th March 2019) - Truelsen, T.; Hansen, K.; Andersen, G.; Sørensen, L.; Madsen, C.; Diaz, A.; Stavngaard, T.; Hundborg, H. H.; Højgaard, J.; Hjort, N.; Iversen, H. K.; Johnsen, S. P.; et al.
Abstract : Background and purpose: Acute endovascular reperfusion treatment (aERT) of stroke patients with large‐vessel occlusions is efficacious and safe according to several clinical trials. Data on outcome and safety of aERT in daily clinical routine are warranted and, in this study, we present national data from Denmark during 2011–2017. Methods: National data for Denmark from 2011 to 2017 on all aERT procedures in patients with acute ischaemic stroke and computed tomography angiography/magnetic resonance angiography‐verified large‐vessel occlusion were derived from the Danish Stroke Registry, a national clinical quality registry to which reporting is mandatory for all hospitals treating stroke patients. Outcome (modified Rankin Scale score) after 3 months, including time of death, was assessed prospectively based on clinical examination or the Danish Civil Registration System. Results: During the 7 years of observation, a total of 1720 patients were treated with aERT. The annual number of procedures increased from 128 in 2011 to 409 in 2017. The median age was 70 years, 58% were males and median National Institutes of Health Stroke Scale score at baseline was 16. Median time from symptom onset to groin puncture was 238 min with a decreasing trend during the years. Successful recanalization was reported in 1306 (76%) patients. At 3‐month follow‐up, an modified Rankin Scale score of 0–2 was reported in 46% of patients, whereas 14% of patients had died. Conclusion: Routine data on aERT in acute ischaemic stroke in Denmark from 2011 to 2017 suggest that the procedure is safe and efficacious.